2010
DOI: 10.1007/s12032-010-9641-x
|View full text |Cite
|
Sign up to set email alerts
|

Pro-apoptotic protein BIM in apoptosis of glucocorticoid-sensitive and -resistant acute lymphoblastic leukemia CEM cells

Abstract: Although glucocorticoids (GCs) have been used to treat acute lymphoblast leukemia (ALL) for decades, the mechanisms of GC sensitivity and resistance in ALL cells are poorly understood. This study investigated the role and mechanisms of pro-apoptotic protein BIM in apoptosis of GC-sensitive and- resistant ALL cells. The dramatic apoptosis was observed in GC-sensitive CEM-C7 cells after incubated with DEX for 48 h, while not in GC-resistant CEM-C1 cells. The significant up-regulation of BIM in CEM-C7 cells induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 26 publications
3
24
0
1
Order By: Relevance
“…Decreased induction of prednisolone-responsive genes upon TBL1XR1 knockdown was also observed upon a shorter 3-h prednisolone exposure (data not shown). Decreased expression of pro-apoptotic protein BIM has been associated with glucocorticoid resistance in ALL (35,36). BIM induction by prednisolone was not effected by TBL1XR1 knockdown (Fig.…”
Section: Tbl1xr1 Knockdown Results In Resistance Tomentioning
confidence: 91%
See 1 more Smart Citation
“…Decreased induction of prednisolone-responsive genes upon TBL1XR1 knockdown was also observed upon a shorter 3-h prednisolone exposure (data not shown). Decreased expression of pro-apoptotic protein BIM has been associated with glucocorticoid resistance in ALL (35,36). BIM induction by prednisolone was not effected by TBL1XR1 knockdown (Fig.…”
Section: Tbl1xr1 Knockdown Results In Resistance Tomentioning
confidence: 91%
“…The induction of BIM upon prednisolone exposure is not reduced by TBL1XR1 knockdown. Because BIM induction is important for prednisolone-induced apoptosis (35,36), BIM induction may account for remaining levels of prednisolone-induced apoptosis observed in the TBL1XR1 knockdown lines. TBL1XR1 is responsible for maintaining appropriate levels of the corepressor NCoR1 (11,31), and decreased levels of TBL1XR1 result in a reciprocal increased level of NCoR1.…”
Section: Discussionmentioning
confidence: 99%
“…By activating the glucocorticoid response element in the nucleus, apoptosis genes are activated by transcription or regulatory factors (nuclear factor-kB or activator protein-1) and transcription is activated. Expression of growth genes is thereby inhibited, resulting in cell apoptosis (Zhao et al, 2011). Studies confirmed that an anomaly at any link in this pathway can lead to GC-resistance (Bachmann et al, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…Recent studies of the pro-apoptotic protein BIM, which is involved in the apoptosis of glucocorticoid-sensitive (CEM-C7) and -resistant (CEM-C1) acute lymphoblastic leukemia CEM cells, have shown that treatment with dexamethasone plus RU486 blocked apoptosis and BIM expression in CEM-C7 cells [65]. P38MAPK-blocking pharmacon SB203580 also significantly inhibits the up-regulation of BIM in CEM-C7 cells [65].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies of the pro-apoptotic protein BIM, which is involved in the apoptosis of glucocorticoid-sensitive (CEM-C7) and -resistant (CEM-C1) acute lymphoblastic leukemia CEM cells, have shown that treatment with dexamethasone plus RU486 blocked apoptosis and BIM expression in CEM-C7 cells [65]. P38MAPK-blocking pharmacon SB203580 also significantly inhibits the up-regulation of BIM in CEM-C7 cells [65]. This evidence suggests that the absence of BIM up-regulation is one of the important mechanisms underlying glucocorticoid resistance, and glucocorticoid-GCR conjugation is indispensable in both glucocorticoid-induced apoptosis and BIM up-regulation.…”
Section: Discussionmentioning
confidence: 99%